Strengthening Economic Evaluation for Multisectoral Strategies (SEEMS) – Nutrition: Common Approach Guidance Document - Levin, Carol; Tokos Harp, Lorna; Crocker, J.; Wun, J.; Kemp, C.; Choo, E.; Margolies, Amy; Gelli, Aulo (University of Washington, 2023)
Combating malnutrition requires a coordinated effort across sectors. While there is a growing body of evidence on what works to improve maternal and child nutrition, comparable evidence on the costs and cost-effectiveness of multisectoral nutrition strategies has been limited (Keats et al 2021, Ruel et al. 2018, Swinnen et al. 2018 and Wun et al. 2022).